The breakthrough of Bedouin women in Northern Israel – a conflict between generations - Ayada, Adel (Kultura-Społeczeństwo-Edukacja, 2018)
The article examines the breakthrough of Bedouin women in Northern Israel, based on the testimony of twenty young Bedouin women who did not accept the ‘traditional’ role of the woman, in the family in particular and in Bedouin society in the village in general. This group of women succeeded in breaking the boundaries of the tribe and struggled for the right to complete high school and even to study in the institutions of higher education.